Artificial Intelligence (Ai) For Talent Acquisition (Ta) In The Manufacturing Sector Of Pakistan (Journal of Namibian Studies : History Politics Culture, 2022)
The study examined the adoption of AI-enabled talent acquisition towards HR or talent acquisition manager satisfaction in the manufacturing sector of Pakistan based on the decision-maker technology-organization-environment (D-TOE) framework. 219 responses have been collected from the HR and talent acquisition managers of manufacturing firms in Karachi using a nonprobability purposive sampling technique, and a five-point Likert scale questionnaire has been used for data collection. The study has employed the PLS-SEM technique for data analysis using SmartPLS v4. The results showed that the adoption of AI-enabled talent acquisition has a positive effect on HR/TA manager's satisfaction; in addition, cost-effectiveness, relative advantage, top management support, competitive pressure, and support from AI vendors have a positive effect on the adoption of AI-enabled talent acquisition whereas orientation towards AI adoption has weak positive effect on adoption of AI-enabled talent acquisition. However, security and privacy concerns, HR readiness, and task-technology fit do not affect adopting AI-enabled talent acquisition. Moreover, adopting AI-enabled talent acquisition positively mediates between all exogenous constructs and HR/TA manager's satisfaction except security and privacy concerns, HR readiness, and task-technology fit. HR managers must also consider the AI technology’s compatibility and suitability for TA functions according to the organization’s requirements when acquiring AIT for TA.